Analisis Sosiolek Dan Fungsiolek Pada Film Pendek Tilik Karya Wahyu Agung Prasetyo - Herawati, Yuke Elvin (sarasvati, 2025)
This study aims to analyze the use of sociolect and functolect in the short film Tilik by Wahyu Agung Prasetyo. Sociolect refers to the variation of language used by individuals in a particular social context, while functolect is a variation of language that appears based on the function or purpose of communication. The film Tilik depicts social dynamics, through the dialogue in this film, there is a representation of various sociolects used by the characters according to social status, age, background, and relationships between individuals, such as the use of slang, regional languages, and formal language. This study found that sociolect variation plays an important role in depicting the characters and social contexts in the film. Younger characters use slang and informal language, while older ones tend to use more formal or traditional language. Meanwhile, functolect can be seen in the way characters use language to achieve certain goals, such as providing information, expressing feelings, or building social relations. The results of this study indicate that the film Tilik is not only an audiovisual work of art, but also a means to study how language variation is used in a broader social context. The diversity of languages used in this film reflects the social diversity that exists in Indonesian society.